Effect of Radiation Interception and Canopy Temperature on Growth, Yield and Quality in Banana Cv. Grande Naine (AAA) under Different Planting Densities - ., Lanuakum; Yepthomi, Graceli I; Maiti, C S (Journal of Horticultural Sciences, 2015)
A study was made to test the effect of radiation interception and canopy temperature under different planting densities [T1- 1.5m x 1.5m (4,444 plants/ha); T2- 2m x 2m (2500 plants/ha); T3- 1.5m x 2.5m (2666 plants/ha); T4- 2m x 2.5m (2000 plants/ha); T5- 2.5m x 2.5m (1600 plants/ha)] on growth, yield and quality in banana cv. Grande Naine. With an increase in planting density, plant height increased significantly. Pseudostem was tallest in the closest spacing, viz., 1.5m x 1.5m (T1), and was shortest in the widest spacing, 2.5m x 2.5m (T5). T1 treatment (1.5m x 1.5m) recorded the least average-canopy-temperature (25.80°C/day) from the flowering to the harvest. T5 recorded the maximum average-radiation-interception, with a value of 432.16 lux/8 hr/day; whereas, T1 recorded minimum average-radiation-interception of 219.58 lux/8 hr/day. Significant influence of spacing was seen on yield /ha. Plants grown under higher density yielded comparatively higher yield (82.65 t/ha) under a spacing of 1.5m x 1.5m (T1). It is thus seen that growth parameters (pseudostem height and number of leaves) and yield/ha in banana was superior at a higher density (1.5m x 1.5m); whereas, in terms of quality of fruit (TSS and total sugar content) spacing of 2.5m x 2.5m was superior. This indicates a positive influence of radiation interception and canopy temperature in banana production.
Keywords: Banana; Grande Naine; Radiation Interception; Canopy Temperature; High-Density Planting